The Effect of the Number Heads Together (NHT) Learning Model on Critical Thinking in Geography Subjects at SMA Angkasa 1 Jakarta - Desti Aulia Fitri; Arlina Arlina (Edumaspul: Jurnal Pendidikan, 2023)
One of the educational challenges is the lack of a strong learning process in the classroom, students are not encouraged to develop thinking skills. As a result, a teacher must take a step forward. The learning process needs to be changed so that students become the center of learning and can be achieved in various ways, including the use of the Numbered Head Together (NHT) learning model. The aim of this research is to determine the effect of the Number Heads Together (NHT) learning model on critical thinking in Geography subject at Angkasa 1 Jakarta High School. The research method uses quasi-experimental research (Quasi Experiment). The research subjects consisted of two classes, namely the experimental class and the control class. Data was collected using a test instrument in the form of a description. The results showed that the t test obtained a significance of 0.180 > 0.05, so there was an influence of the Number Heads Together (NHT) learning model on critical thinking in geography subjects at SMA Angkasa 1 Jakarta. Keywords: Number Heads Together (NHT) Model, Critical Thinking, Geography Learning